Internalized Sexual Minority Stigma is Associated With HIV Testing Behavior Among Chinese Men Who Have Sex With Men: A Cross-Sectional Study. (2nd September 2021) - Chi, Yuanyuan; Huang, Daoping; Pachankis, John; Valimaki, Maritta; Shen, Yan; Li, Xianhong
Abstract: Although studies have examined the relationship between HIV-related stigma and HIV testing among men who have sex with men (MSM) in China, there is still a lack of knowledge regarding whether sexual minority stigma and HIV testing are associated. The purpose of this study was to identify the association between sexual minority- and HIV-related stigmas with HIV-testing behavior. A cross-sectional study was conducted in the Hunan Province of China. After controlling for covariates, the multivariate analyses showed that high internalized sexual minority stigma was negatively associated with HIV testing behavior in the previous year. However, anticipated sexual minority- and HIV-related stigmas were not associated with HIV-testing behavior. Findings suggest that internalized sexual minority stigma should be addressed in health care settings to encourage MSM to seek HIV testing services, especially considering the continuing HIV epidemic among MSM in China.